The Effects of BMP-2, miR-31, miR-106a, and miR-148a on Osteogenic Differentiation of MSCs Derived from Amnion in Comparison with MSCs Derived from the Bone Marrow - Sirikul Manochantr; Kulisara Marupanthorn; Chairat Tantrawatpan; Pakpoom Kheolamai; Duangrat Tantikanlayaporn; Prakasit Sanguanjit (Stem Cells International)
Mesenchymal stromal cells (MSCs) offering valuable anticipations for the treatment of degenerative diseases. They can be found in many tissues including amnion. MSCs from amnion (AM-MSCs) can differentiate into osteoblast similar to that of bone marrow-derived MSCs (BM-MSCs). However, the ability is not much efficient compared to BM-MSCs. This study aimed to examine the effects of BMP-2 and miRNAs on osteogenic differentiation of AM-MSCs compared to those of BM-MSCs. The osteogenic differentiation capacity after miRNA treatment was assessed by ALP expression, ALP activity, and osteogenic marker gene expression. The results showed that the osteogenic differentiation capacity increased after BMP-2 treatment both in AM-MSCs and BM-MSCs. MiR-31, miR-106a, and miR-148a were downregulated during the osteogenic differentiation. After transfection with anti-miRNAs, ALP activity and osteogenic genes were increased over the time of differentiation. The data lead to the potential for using AM-MSCs as an alternative source for bone regeneration. Moreover, the information of miRNA expression and function during osteogenic differentiation may be useful for the development of new therapeutics or enhanced an in vitro culture technique required for stem cell-based therapies in the bone regeneration.